(untitled) (Journal of Science and Technology, 2016)
Ethanolic crude extract, volatile oil and the peel powder of sweet orange (Citrus sinensis) were evaluated for their efficacy against the bean weevil (Callosobruchus maculatus Fab.). The peel powder was evaluated at concentrations of 5.0 g, 7.5 g, and 10.0 g /50 g of cowpea seeds. Ethanolic crude extract and volatile oil were evaluated at concentrations of 0.1 ml, 0.2 ml and 0.3 ml / 50 g of cowpea seeds. Mortality count was recorded at 24, 48, and 72 hours post treatment. F1 adult emergence was also counted after 4 weeks of storage. All treatments exhibited significantly (p < 0.05) higher mortalities and lower F1 adult emergence than the untreated control. Ethanolic crude extract gave the least F1 adult emergence compared with other treatments and control. At the concentration of 0.3 ml/ 50 g of Ethanolic crude extract, there was no F1 adult emergence. Ethanolic crude extract at this concentration gave adequate protection to stored cowpea seeds.